SUBSTANTIATION OF REAMBERIN APPLICATION IN COMPLEX TREATMENT OF PATIENTS WITH ACUTE SMALL BOWEL OBSTRUCTION - V. D. Skripko; A. L. Kovalenko; V. A. Zaplutanov (Вестник хирургии имени И.И. Грекова)
The study evaluated the efficacy of reamberin in complex treatment of patients with acute small bowel obstruction. Methods. The research is based on the results of complex examination of 202 patients with acute small bowel obstruction (ASBO). The patients were hospitalized in Ivano-Frankovsk central municipal clinical hospital at the period from 2009 to 2015. The patients were divided into two groups according to the method of treatment. The complex treatment using common method was applied for the first group of 100 patients with ASBO. The complex treatment using common method and reamberin intravenously (800 ml/day) during 7 days was applied for the second group of 102 patients. Results. The application of reamberin reduced a lot of indices such as leukocytic intoxication, intoxication index, level of middle mass molecule, formation of malonic dialdehyde. The drug stimulated antioxidant system and normalized organ-specific liver enzymes. Conclusions. The application of reamberin is pathogenetically validated in cases of ASBO.